Field Monitoring and Numerical Simulation Analysis of Deep Shaft Concrete Wall Support - Hongguang Ji; Zhen Fu; Yuezheng Zhang; Chunrui Zhang (Geofluids)
Affected by faults, fractures, and high ground stress, the deep shaft wall is prone to deformation and fracture, which affects the safety of mine construction. To investigate the stress and deformation of the shaft wall at the horsehead gate connection, the force-measuring bolt and vibrating string concrete strain gauges were installed for on-site monitoring prior to the shaft wall pouring. It was found that the concrete strains and forces on the shaft wall were divided into four stages during the tedious shaft construction. The measured data showed that the maximum pressure and tension on the shaft wall were 4.5 MPa and 1.3 MPa, respectively, the maximum axial compressive and tensile strains were -500 με and 1700 με, and the maximum circumferential compressive and tensile strains were -1000 με and 400 με. During the shaft excavation construction, there is a tensile state in the shaft wall at the connection of the horsehead gate. In addition, there will be uneven stress in the concrete support structure and a sharp increase in the local stress of the shaft wall. Therefore, the problem of supporting the wall of deep shafts is undoubtedly a significant challenge in the construction of shafts. The numerical simulation results combined with the on-site monitoring of the layers show that stress concentrations occur at the lower end of the shaft wall and the interconnections between the walls during the excavation process. Therefore, it is essential to pay attention to the stress values in the lower part of the wall when constructing deeper sections to avoid stress concentrations and pay attention to the construction quality when constructing the wall joints to meet the wall’s safety needs support.